2021 international consensus statement on optical coherence tomography for basal cell carcinoma: image characteristics, terminology and educational needs. (9th February 2022) - Fuchs, C.S.K.; Ortner, V.K.; Mogensen, M.; Rossi, A.M.; Pellacani, G.; Welzel, J.; Mosterd, K.; Guitera, P.; Nayahangan, L.J.; Johnsson, V.L.; Haedersdal, M.; Tolsgaard, M.G.; et al.
Abstract: Background: Despite the widespread use of optical coherence tomography (OCT) for imaging of keratinocyte carcinoma, we lack an expert consensus on the characteristic OCT features of basal cell carcinoma (BCC), an internationally vetted set of OCT terms to describe various BCC subtypes, and an educational needs assessment. Objectives: To identify relevant BCC features in OCT images, propose terminology based on inputs from an expert panel and identify content for a BCC‐specific curriculum for OCT trainees. Methods: Over three rounds, we conducted a Delphi consensus study on BCC features and terminology between March and September 2020. In the first round, experts were asked to propose BCC subtypes discriminable by OCT, provide OCT image features for each proposed BCC subtypes and suggest content for a BCC‐specific OCT training curriculum. If agreement on a BCC‐OCT feature exceeded 67%, the feature was accepted and included in a final review. In the second round, experts had to re‐evaluate features with less than 67% agreement and rank the ten most relevant BCC OCT image features for superficial BCC, nodular BCC and infiltrative and morpheaphorm BCC subtypes. In the final round, experts received the OCT‐BCC consensus list for a final review, comments and confirmation. Results: The Delphi included six key opinion leaders and 22 experts. Consensus was found on terminology for three OCT BCC image features: (i) hyporeflective areas, (ii) hyperreflective areas and (iii) ovoid structures. Further, the participants ranked the ten most relevant image features for nodular, superficial, infiltrative and morpheaform BCC. The target group and the key components for a curriculum for OCT imaging of BCC have been defined. Conclusion: We have established a set of OCT image features for BCC and preferred terminology. A comprehensive curriculum based on the expert suggestions will help implement OCT imaging of BCC in clinical and research settings.